Application of nonlinear dynamics theory to understanding normal and pathologic voices in humans - Švec, Jan G; Zhang, Zhaoyan (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2025)
The theory of nonlinear dynamics was introduced to voice science in the 1990s and revolutionized our understanding of human voice production mechanisms. This theory elegantly explains highly complex phenomena in the human voice, such as subharmonic and rough-sounding voice, register breaks, and intermittent aphonic breaks. These phenomena occur not only in pathologic, dysphonic voices but are also explored for artistic purposes, such as contemporary singing. The theory reveals that sudden changes in vocal fold vibratory patterns and fundamental frequency can result from subtle alterations in vocal fold geometry, mechanical properties, adduction, symmetry or lung pressure. Furthermore, these changes can be influenced by interactions with supraglottal tract and subglottal tract resonances. Crucially, the eigenmodes (modes of vibration) of the vocal folds play a significant role in these phenomena. Understanding how the left and right vocal fold eigenmodes interact and entrain with each other, as well as their interplay with supraglottal tissues, glottal airflow and acoustic resonances, is essential for more sophisticated diagnosis and targeted treatment of voice disorders in the future. Additionally, this knowledge can be helpful in modern vocal pedagogy. This article reviews the concepts of nonlinear dynamics that are important for understanding normal and pathologic voice production in humans.This article is part of the theme issue 'Nonlinear phenomena in vertebrate vocalizations: mechanisms and communicative functions'.
Keywords: poruchy hlasu; nelineární dynamika; Voice Disorders; vocal fold eigenmodes; Humans; dysphonia; Vocal Cords; Nonlinear Dynamics; Voice; hlasové řasy; hlas; singing; entrainment; voice production; lidé; nonlinear phenomena